2017
DOI: 10.2147/jir.s138431
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro model of renal inflammation after ischemic oxidative stress injury: nephroprotective effects of a hyaluronan ester with butyric acid on mesangial cells

Abstract: BackgroundAcute kidney injury, known as a major trigger for organ fibrosis and independent predictor of chronic kidney disease, is characterized by mesangial cell proliferation, inflammation and unbalance between biosynthesis and degradation of extracellular matrix. Therapeutic approaches targeting the inhibition of mesangial cell proliferation and matrix expansion may represent a promising opportunity for the treatment of kidney injury. An ester of hyaluronic acid and butyric acid (HB) has shown vasculogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Our study showed that renal I/R was associated with a significant increase in cardiac Bax protein value compared to the control group and this was in agreement with others (Liu et al, 2007). Previous studies suggested that oxidative stress and subsequent inflammation have an important role in magnifying the apoptosis in the ischemic organ and distant organ damages (Baraldi et al, 2017). In our study, lithium tetraborate could ameliorate myocardial apoptosis via positive regulation of antioxidant defense and negative regulation of inflammation/oxidative stress signaling pathways.…”
Section: Lithium Tetraborate Reduces the Heart Injury Induced By Rena...supporting
confidence: 54%
“…Our study showed that renal I/R was associated with a significant increase in cardiac Bax protein value compared to the control group and this was in agreement with others (Liu et al, 2007). Previous studies suggested that oxidative stress and subsequent inflammation have an important role in magnifying the apoptosis in the ischemic organ and distant organ damages (Baraldi et al, 2017). In our study, lithium tetraborate could ameliorate myocardial apoptosis via positive regulation of antioxidant defense and negative regulation of inflammation/oxidative stress signaling pathways.…”
Section: Lithium Tetraborate Reduces the Heart Injury Induced By Rena...supporting
confidence: 54%
“…With sodium butyrate administered as a preventative measure, myeloperoxidase activity and entry of inflammatory cells into the lungs are markedly reduced, and these effects are linked to the suppression of proinflammatory cytokines (TNF-alpha and IL-6), HMGB1 expression, and NF-κB activation (Figure ). Sodium butyrate and propionate target the lipopolysaccharide (LPS)-related TLR-4/NF-κB pathway and reduce lung damage caused by LPS stimulated cytokines (including IL-6 and IL-12p40. After being exposed to oxidative stress, hyaluronan ester plus butyric acid therapy promotes apoptosis in mesangial cells, inhibiting cell proliferation via the p38 MAPK pathway . The production of IL-13 and IL-15 by type 2 ILCs is inhibited by butyrate.…”
Section: Role Of Scfas In Sars-cov-2 Therapeuticsmentioning
confidence: 99%
“… 167 169 After being exposed to oxidative stress, hyaluronan ester plus butyric acid therapy promotes apoptosis in mesangial cells, inhibiting cell proliferation via the p38 MAPK pathway. 170 The production of IL-13 and IL-15 by type 2 ILCs is inhibited by butyrate. Furthermore, butyrate suppresses the expression of inflammatory genes post-transcriptionally by downregulating a number of RNA binding proteins.…”
Section: Role Of Scfas In Sars-cov-2 Therapeuticsmentioning
confidence: 99%
“…The TLR 4/NF-κB pathway involved in the LPS is targeted by sodium butyrate, which attenuates the LPS induced lung injury 27 . Hyaluronan ester with butyric acid treatment induces apoptosis in mesangial cells after exposure to oxidative stress and thereby reducing cell proliferation via p38 MAPK pathway 141 . N-(1-carbamoyl-2-phenyl-ethyl) butyramide (FBA), a butyrate releasing compound, confers protection to mice from colitis induced by dextran sodium sulphate by suppressing neutrophils recruitment and subsequent release of pro-inflammatory molecules mediated by HDAC-9/NF-κB inhibition and peroxisome proliferator-activated receptor gamma (PPAR-γ) upregulation 142 .…”
Section: Is Butyrate An Alternative To Dexamethasone?mentioning
confidence: 99%